Certainty-Based Self-Assessment in Higher Education: A Strategy for All? - Remesal, Ana; García-Mínguez, Patricio; Domínguez, Judit; Corral, María José (International Journal of Advanced Corporate Learning (iJAC), 2024)
This study explores students’ behavior in response to a study-learning system during one semester at university, based on the certainty-based marking strategy. The learning support system pursues to encourage diagnostic formative self-assessment. In total, 258 students complete the full study program and respond to an additional sociodemographic questionnaire. An exploratory study was performed. Two individual variables were considered for basic statistical analysis: gender and prior academic experience. Results show progression of students’ confident responses, especially by the third trial. No differences were found with respect to gender. In contrast, strong differences were found related to prior academic experience. These latter results must be taken carefully, in expectance of further research to look for connections with other individual variables.